The Effects of the Vietnam Hunger Eradication and Poverty Reduction Program on Schooling - Marco Bertoni; Quynh Huynh; Lorenzo Rocco (Institute of Labor Economics (IZA), 2019)
This paper studies the effects of the Vietnam Hunger Eradication and Poverty Reduction (HEPR) program on school enrolment, using longitudinal data that span over 15 years and a difference-in-differences research design. We find that early treatment (at age 8) increases children enrolment by about 9 percent. This positive effect disappears by age 15, and is more pronounced in urban areas. In sharp contrast, children receiving treatment later (age 12–15) are more likely to drop out by age 15, especially in rural areas. The decline in enrolment is paralleled by an increase in labor market participation. We interpret these divergent results by age as an unintended effect of another program aimed at fostering vocational training among the 15+ in rural areas. Our findings highlight the importance of integrating different anti-poverty measures to reduce inefficiency and achieve social goals.
Keywords: H52; H53; I24; I32; 330; child poverty; child education; enrolment; Vietnam; poverty reduction